The Use of Bone Morphogenetic Protein in Pediatric Cervical Spine Fusion Surgery: Case Reports and Review of the Literature - Molinari, Robert W. (Global Spine J, 2015)
Study Design Case report. Objective There is a paucity of literature describing the use of bone graft substitutes to achieve fusion in the pediatric cervical spine. The outcomes and complications involving the off-label use of bone morphogenetic protein (BMP)-2 in the pediatric cervical spine are not clearly defined. The purpose of this article is to report successful fusion without complications in two pediatric patients who had instrumented occipitocervical fusion using low-dose BMP-2. Methods A retrospective review of the medical records was performed, and the patients were followed for 5 years. Two patients under 10 years of age with upper cervical instability were treated with occipitocervical instrumented fusion using rigid occipitocervical fixation techniques along with conventionally available low-dose BMP-2. A Medline and PubMed literature search was conducted using the terms “bone morphogenetic protein,” “BMP,” “rh-BMP2,” “bone graft substitutes,” and “pediatric cervical spine.” Results Solid occipitocervical fusion was achieved in both pediatric patients. There were no reported perioperative or follow-up complications. At 5-year follow-up, radiographs in both patients showed successful occipital cervical fusion without evidence of instrumentation failure or changes in the occipitocervical alignment. To date, there are few published reports on this topic. Complications and the appropriate dosage application in the pediatric posterior cervical spine remain unknown. Conclusions We describe two pediatric patients with upper cervical instability who achieved successful occipital cervical fusion without complication using off-label BMP-2. This report underscores the potential for BMP-2 to achieve successful arthrodesis of the posterior occipitocervical junction in pediatric patients. Use should be judicious as complications and long-term outcomes of pediatric BMP-2 use remain undefined in the existing literature.